A Case Report of Rhabdomyosarcoma of Uterine Cervix in a 7-Month-Old Child (BIRDEM Medical Journal, 2017)
Rhabdomyosarcoma is the soft tissue tumor derived from embryonic primary mesenchyme. Neck, head and genitourinary region are the common locations of rhabdomyosarcoma. Here, we report a 7-month-old child who presented with a protruding mass per vaginally. Abdominal examination revealed a 6 cm x 6 cm hard, irregular, non-tender mass at pelvic region. Ultrasound of abdomen showed large heterogenous pelvic mass of uterine origin. Magnetic resonance imaging of whole abdomen revealed an intrapelvic teratoma (9.5 x 7.4 x 10 cm3) with left sided hydronephrotic change as the mass was pressing the rectum and bladder. The child underwent a total hysterectomy. Histopathology result was suggestive of rahbdomyosarcoma of uterus.Birdem Med J 2017; 7(3): 242-244